PENERAPAN MODEL PJBL DALAM PEMBELAJARAN MENULIS TEKS PROSEDUR SEDERHANA BAGI SISWA KELAS TUJUH MTS NEGERI 6 TULUNGAGUNG - AFFANDI, SRI HARIYANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
Research objectives The application of the PjBL model in the practice of writing simple procedural texts is a step in measuring the practice of learning integrated Indonesian language skills, namely learning the skills of writing procedural texts according to the structure and characteristics of the language. The type of procedural text that is assessed is a simple procedural text on how to do something, namely the procedural text on How to Perform Wudu Correctly. How to make something. So the assessment is integrated between making the text according to the structure (introduction & steps) and analyzing errors in the use of linguistic characteristics of the procedural text (command sentences, suggestions sentences, use of number words in the form of measurements). In this regard, Indonesian language teachers utilize the PjBL learning model. With the PjBL model, it is hoped that the learning objectives and assessment practice will be to write simple procedural texts that are useful for students as subjects of learning Indonesian. ABSTRAKTujuan penelitian tindakan kelas berjudul Penerapan model PjBL dalam praktik mnilis teks prosedur sederhana merupakan langkah pengukuran praktik pembelajaran keterampilan berbahasa Indonesia terpadu, yakni pembelajaran keterampilan menulis teks prosedur sesuai struktur dan ciri kebahasaannya. Adapun jenis teks prosedur yang dinilai adalah teks prosedur sederhana cara melakukan sesuatu, yakni teks prosedur Cara Melakukan Wudu Yang Benar. Cara membuat sesuatu. Jadi penilaiannya secara terpadu antara pembuatan teks sesuai struktur (pendahulua& langkah-langkah) dan analisis kesalahan penggunaan ciri kebahasaan teks prosdur diperlukan ( kalimat perintah, kalimat saran, penggunaan kata bilangan berbentuk ukuran). Dalamkaitan ini guru bahasa Indonesia memmanfaatkan model belajar PjBL. Dengan model PjBl diharapkan tujuan pembelajaran dan penilaian praktik menulis teks prosedur sederhana yang bermakan bagi siswa selaku subjek belajar bahasa Indonesia.